The Effect of Audit Delay, Firm Risk, Profitability, and Firm Complexity on Audit Fees - Ferdi Agung Himawan D; Sintia Hafifah (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2026)
This study aims to examine the effects of Audit Delay, Corporate Risk, Profitability, and Company Complexity on Audit Fees among manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. The study employs a quantitative research approach using a purposive sampling technique, resulting in a sample of 48 companies. Secondary data were obtained from the companies' annual financial statements. The hypotheses were tested using multiple linear regression analysis. The results indicate that Audit Delay has a positive and significant effect on Audit Fees. Corporate Risk has a negative and significant effect on Audit Fees. Profitability has a positive and significant effect on Audit Fees, while Company Complexity also has a positive and significant effect on Audit Fees. Simultaneously, all four independent variables significantly influence Audit Fees. The findings are expected to provide valuable insights for corporate management, auditors, and investors in determining and evaluating appropriate audit fees. Keywords: Audit Delay, Corporate Risk, Profitability, Company Complexity, Audit Fee